Social Media, Vaccines, and Partisan Division of Health Information. Issue 1 (13th October 2021) - Hagen, Loni; Greyson, Devon; Fox, Ashley; Koltai, Kolina; Dumas, Catherine
Abstract: Vaccine confidence and uptake is essential to achieving herd immunity levels sufficient to end the COVID‐19 pandemic; however, polarized and partisan discussion on vaccines have increased the difficulty of achieving sufficient vaccine coverage in the population. As individual's health information seeking behaviors diversify, studies suggest that social media is a major "battle ground" for shaping attitudes toward vaccines. Interdisciplinary experts on vaccine discourse will discuss the information context of the vaccine debate, political influence, and attitudes towards science and vaccines against the backdrop of social media. This panel is expected to contribute to the field of information science by invoking a conversation on social media, an important information communication technology, as a field of study that inter‐connects the most current vaccine conversation with theories of partisan behavior of health information and affordance of technology. This panel is sponsored by SIG SM.